2014
DOI: 10.1371/journal.pone.0090584
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Functional Consequences and Ongoing Cerebral Inflammation after Subarachnoid Hemorrhage in the Rat

Abstract: Subarachnoid hemorrhage (SAH) represents a considerable health problem with an incidence of 6–7 per 100.000 individuals per year in Western society. We investigated the long-term consequences of SAH on behavior, neuroinflammation and gray- and white-matter damage using an endovascular puncture model in Wistar rats. Rats were divided into a mild or severe SAH group based on their acute neurological score at 24 h post-SAH. The degree of hemorrhage determined in post-mortem brains at 48 h strongly correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 50 publications
(67 reference statements)
3
64
0
Order By: Relevance
“…27,28 In our study, we found histological changes 7 days after SAH, and comparison of corpus callosum thickness of both hemispheres indicated white matter thinning ipsilateral to the SAH induction site. Similar observations were reported recently in a rat model.…”
Section: March 2015supporting
confidence: 56%
See 2 more Smart Citations
“…27,28 In our study, we found histological changes 7 days after SAH, and comparison of corpus callosum thickness of both hemispheres indicated white matter thinning ipsilateral to the SAH induction site. Similar observations were reported recently in a rat model.…”
Section: March 2015supporting
confidence: 56%
“…Similar observations were reported recently in a rat model. 27 One possible explanation for this lateralization effect may be the presence of a more pronounced vasospasm near the initial bleeding site. 29 Many studies have investigated the role of DC in traumatic brain injury 10,11 and malignant MCA infarction, 12,13 and the beneficial effects of DC in malignant MCA infarction have led to the recommendation of including DC in current treatment guidelines.…”
Section: March 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term neuroinflammation is strongly induced gray-and white-matter damage, which contributes to long-term sensorimotor impairment [57]. Therefore, a therapeutic strategy for against the neuroinflammation is able to improve the neurological and sensorimotor deficits [58].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation: Is studied as the activation of inflammatory molecules and cytokines 23, 24 . Inflammation is observed as adhesion of platelet aggregates and neutrophil to the walls of small cerebral vessels 2527 and as increased immunoreactivity to nestin, ED1, OX6, intercellular adhesion molecule 1, and tumor necrosis factor 23 .…”
Section: Introductionmentioning
confidence: 99%